Potential of Lactobacillus casei Shirota Strain Probiotic Toward Total Cholesterol Levels and Sod Activity in Rat with High Cholesterol Diet - Kiswanti Surya Utami; Aulanni'am Aulanni’am; Chanif Mahdi (Universitas Jenderal Soedirman, 2017)
Probiotic of Lactobacillus casei Shirota strain is lactic acid bacteria that have benefits to enhance immunity system, as an antioxidant and has the ability to decrease the cholesterol level. The aim of this study was to determine the potential of Lactobacillus casei Shirota strain probiotic toward total cholesterol decreasing and SOD activity increasing in rats’ aorta with a high-cholesterol diet. This study used 25 male rats of Rattus novergicus Wistar strain that will be divided into 5 groups. The 1st group as the negative control, and the 2nd group as positive control. The positive control group was induced by high-cholesterol diet contained quail egg yolk, pure cholesterol, cholic acid and waste oil that were given for 3 weeks. The 3rd, 4th and 5th group were treated by probiotic Lactobacillus casei Shirota strain with variation dose of 3.6 x 107, 7.3 x 107 and 10.9 x 107 cells/kg bodyweight/day. The results showed that probiotic of Lactobacillus casei Shirota strain therapy dose of 10.9 x 107 cells/kg bodyweight/day can decrease the total blood cholesterol of rats’ serum that were given with high-cholesterol diet of about 32.0%. In addition, the probiotic of Lactobacillus casei Shirota strain therapy also increase the activity of SOD about 50.70%.